Sustainable phase change material developments for thermally comfortable smart buildings: A critical review - Yadav, Aman; Mahendran, Samykano; Pandey, Adarsh Kumar; Natarajan, Sendhil Kumar; Vasudevan, Gopi; Muthuvairavan, Guna; Suraparaju, Subbarama Kousik (Elsevier, 2024)
The building industry is crucial in consuming vast quantities of energy in the modern era. Therefore, it is essential to carry out cutting-edge alterations to reduce energy usage and improve the energy performance of buildings. Thermal energy storage (TES) has become a principal point of investigation for researchers worldwide. Particularly in Phase change materials (PCMs) due to their significant advantages in strengthening energy efficiency, satisfying thermal comfort, and mitigating environmental pollution. Also, TES integrated with PCMs earns outstanding attention for its pivotal role in advancing energy conservation in building heating and cooling applications. Further, PCMs are incorporated in residential, commercial, and other building heating and cooling applications based on their reliance on heating and cooling methods. Hence, the present study provides an up-to-date analysis of recent academic research on TES management that utilizes PCMs for building heating and cooling. It explores the properties, characterization, and selection criteria determining their suitability for usage in building applications. Additionally, the thermal properties, incorporation techniques, factors that affect a building's energy efficiency, drawbacks of PCMs, and their alterative actions in building climate control are critically discussed. In addition, PCMs possible solutions for building applications and the policies of the PCMs to promote building thermal comfort are discussed comprehensively. Moreover, research investigations have demonstrated that incorporating PCMs has enhanced the energy efficiency of buildings, reduced energy costs, boosted heat retention, and maintained conformance to thermal comfort regulations. Therefore, PCMs integration in buildings can provide efficient solutions to issues arising from energy shortages, carbon emissions, and the significant environmental concerns they raise.